PENGARUH EFFECTIVE TAX RATE, ARUS KAS, DAN KEPEMILIKAN MANAJERIAL TERHADAP KEBIJAKAN DIVIDEN (Studi Empiris Pada Perusahaan Barang Konsumsi yang Terdaftar di BEI Periode 2017-2021) - Julian Muhammad Hasan; Liana Dwi Septiningrum (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2023)
This study aims to analyze the effective tax rate, cash flow and managerial ownership of dividend policy. This study uses a quantitative method and uses secondary data from consumer sector companies listed on the Indonesia Stock Exchange in 2017-2021. Hypothesis testing was carried out using the Eviews 10 application. There were 85 company data samples selected using a purposive sampling technique using several criteria according to research needs. Based on the test results, it was revealed that partially the effective tax rate and managerial ownership variables had an effect on dividend policy, while the cash flow variable had no effect on dividend policy. The results of the simultaneous effective tax rate, cash flow, and managerial ownership affect dividend policy.